Multi-scale hybrid spherical graphite composites: a light weight thermal interface material with high thermal conductivity and simple processing technology. Issue 45 (13th October 2022) - Yan, Dingbang; Li, Zexian; Kong, Nizao; Huang, Min; Tian, Yexin; Ye, Chong; Fu, Liqin; Wen, Bingjie; Liu, Jinshui; Tan, Ruixuan; Han, Fei
Abstract : A new carbon-based thermal conductive filler, a new calculation method of multi-scale spherical particle mixing and a model for predicting thermal conductivity by tap density. Abstract : In consideration of low density and high intrinsic thermal conductivity, spherical graphite powders can act as promising fillers for light weight thermal interface materials. Herein, spherical artificial graphite derived composites exhibit a similar thermal conductivity and significantly reduced bulk density compared with traditional Al2 O3 -derived composites. Further, based on the particle packing theory, an innovatively optimized calculation method has been proposed by introducing the quadratic programming method into the traditional calculation method to acquire the optimum formulation of multi-scale spherical graphite particles. The thermal conductivity of the optimum formulation-derived composites attains 1.994 W m −1 K −1, which is 1.72 times higher than that of the single particle size-derived composites (1.156 W m −1 K −1 ), accompanied by a low density of 1.812 g cm −3 vs. the 2.31 g cm −3 of the traditional Al2 O3 -derived composites. Besides, the relationships between the tap density of the graphite powders, thermal conductivity and maximum filling content of the composites are creatively established, which are available for predicting the thermal conductivities of composites by simply testing the tap density of the fillers. This present work provides an instructional strategy to optimize spherical filler particles for thermal management of electronic devices.